Thermal Analysis of a Building Integrated Photovoltaic (BIPV) System - Agathokleous, Rafaela; Kalogirou, Soteris A. (My University, 2016)
During the last few years photovoltaic (PV) panels are increasingly incorporated into the construction of buildings for generating electrical power (BIPV systems) or both electrical and thermal energy (BIPV/T systems). The integration creates heat in the gap between the PVs and the building’s skin, which if not removed to be used to cover part of the heating load of the building (winter) or to the atmosphere (summer), it decreases the efficiency of the PVs and increases the cooling loads of the buildings in summertime. This study aims to evaluate the thermal behaviour of a BIPV system in order to decide whether natural ventilation of the air behind the PV is adequate to cool it down and remove the excess heat. The examination of the effect of the air gap of a BIPV system as well as the slope of the system or the amount of solar radiation are very important parameters as they can lead to better understanding of the conditions that allow the higher efficiency of the PV panels and accordingly higher efficiency of the BIPV system. The investigation of the above parameters is done experimentally in a laboratory with a large scale solar simulator (SS) and a representative apparatus of a BIPV system, able to change the air gap of the duct and the slope in order to simulate roof or façade installation. The experimental results are compared with 3D modelling simulation results obtained using COMSOL Multiphysics software.
Keywords: Solar simulator; BIPV; Integration; Thermal behaviour; Photovoltaics; BIPV/T